2013
DOI: 10.1109/tro.2012.2234311
|View full text |Cite
|
Sign up to set email alerts
|

Salamandra Robotica II: An Amphibious Robot to Study Salamander-Like Swimming and Walking Gaits

Abstract: Abstract-In this paper we present Salamandra robotica II, an amphibious salamander robot, that is able to walk and swim. The robot has four legs and an actuated spine that allow it to perform anguilliform swimming in water and walking on ground. The paper first presents the new robot hardware design, which is an improved version of Salamandra robotica I. We then address several questions related to body-limb coordination in robots and animals that have a sprawling posture like salamander and lizards as opposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
159
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 220 publications
(165 citation statements)
references
References 32 publications
4
159
0
2
Order By: Relevance
“…Therefore, the narrow range of bending angles in salamanders may be a result of the trade-off between stride length and energy efficiency. It is worth noting that Crespi et al (2013) reported striking similarities in the performance and kinematics of Salamandra robotica II and real salamanders which is also evident in Figs. 9 and 10.…”
Section: Terrestrial Steppingsupporting
confidence: 59%
See 4 more Smart Citations
“…Therefore, the narrow range of bending angles in salamanders may be a result of the trade-off between stride length and energy efficiency. It is worth noting that Crespi et al (2013) reported striking similarities in the performance and kinematics of Salamandra robotica II and real salamanders which is also evident in Figs. 9 and 10.…”
Section: Terrestrial Steppingsupporting
confidence: 59%
“…Lateral bending during forward walking Experiments with a kinematic model of Salamandra robotica II and the real robot showed that higher trunk bending yields greater stride length (Karakasiliotis and Ijspeert 2009;Crespi et al 2013. However, both the model and the robot showed that there is a maximum value of bending after which the stride length starts to decay (Fig.…”
Section: Terrestrial Steppingmentioning
confidence: 99%
See 3 more Smart Citations